Disiplin Kerja Aparatur Sipil Negara Pada Dinas Pangan Provinsi Sulawesi Tengah - Jisman Jisman; Debi Purnama (Jurnal ADMINISTRATOR, 2021)
Employee discipline at the Central Sulawesi Provincial Food Service has not been implemented optimally. The purpose of this research is to find out how the Discipline of the Work of the State Civil Apparatus at the Food Service is, which causes the less than optimal discipline of the Work of the State Civil Apparatus at the Food Service. The type of research used was qualitative and purposive informant selection technique with 5 selected informants. Data collection techniques were carried out through interviews, observation and documentation. Data analysis techniques through the stages of data editing, categorization, interpretation of the meaning of the data and drawing conclusions. The theory used is the George C Edwards III policy implementation model with the variables in the form of communication, resources, disposition and bureaucratic structure. The results show that the implementation of disciplinary policies at the Food Service has not been carried out properly due to the lack of optimal work discipline of the State Civil Apparatus at the Food Service, the lack of socialization, communication methods or techniques that are built so that they are less effective, lack of leadership commitment to consistently and consistently apply discipline , lack of exemplary leadership in implementing discipline, lack of strict application of rewards and punishments, lack of coordination and collaboration in implementing discipline among structural officials or direct supervisors of employees, and lack of understanding of SOPs for implementing Government Regulation No. 53 of 2010 by State Civil Apparatus at the Food Service.